Building the Veterans Experience Office: CX and the Public Sector. (9th July 2019) - Morton, Barbara C.; Becker, Lee
Abstract : Building a Veterans Experience Office—with the goal of being the #1 customer experience office in the federal government—required a completely new view at the enterprise level. Building leadership at the Veterans Administration—with the help of human‐centered design.